Analysis of the p-i-n-structures Electrophysical Characteristics Influence on the Spectral Characteristics Sensitivity - V.N. Murashev; S.Yu. Yurchuk; S.A. Legotin; V.P. Yaromskiy; Yu.V. Osipov; V.P. Astahov; D.S. El’nikov; S.I. Didenko; O.I. Rabinovich; K.A. Kuz’mina (Журнал нано- та електронної фізики)
In this paper the simulation of the silicon p-i-n-photodiodes spectral sensitivity characteristics was carried out. The analysis of the semiconductor material characteristics (the doping level, lifetime, surface recombination velocity), the construction and operation modes on the photosensitive structures characteristics in order to optimize them were investigated.